Renewable energy technology uptake: Public preferences and policy design in early adoption - Sanghamitra Chattopadhyay Mukherjee; Tensay Hadush Meles; Lisa Ryan; Séin Healy; Robert Mooney; Lindsay Sharpe; Paul Hayes (University College Dublin, UCD Centre for Economic Research, 2020)
This paper aims to understand what motivates the adoption of key renewable energy technologies (RET) in early adopter markets. Electrification of heat and transport, through the deployment of heat pumps, electric vehicles and solar photovoltaic panels, combined with renewable sources of electricity is a key strategy for policymakers to combat climate change. Notwithstanding their social benefits, uptake remains low. Thus, targeted policy measures are needed to address this. We conduct a survey of a nationally representative sample of Irish households to better understand the motivations behind RET adoption and find fundamental differences between adopters and non-adopters. Current adopters tend to be younger, highly educated, of higher socio-economic status, and are likely to live in newer buildings of generous size. While non-adopters self-report as being more sustainable, adopters appear to be stronger believers that their own decisions impact climate change. Thus, environmental attitudes are an insufficient predictor of uptake. Instead, poor understanding of new technologies often inhibits uptake. Word-of-mouth recommendation matters greatly in communicating the use and benefits of new technology as evident from the significantly larger social networks that adopters enjoy. With this information, a range of monetary and non-monetary policy incentives can be designed according to public preferences.
Keywords: D1; D9; O3; Q4; 330; Household survey; technology adoption policy; heat pumps; solar PV; electric vehicles; consumer behaviour